A multitude of all peoples: engaging ancient Christianity's global identity - Bantu, Vince L. (InterVarsity Academic, 2020)
"Christianity is not becoming a global religion-it has always been one. Vince Bantu surveys the geographic range of the early church's history, investigating the historical roots of the Western cultural captivity of the church and the concurrent development of diverse expressions of Christianity across Africa, the Middle East, and Asia"–
Keywords: Church history; Globalization; Primitive and early church; ca. 30-600; Religious aspects Christianity